Cover Image, Volume 7, Issue 3. (May 2016) - McNeil, Bonnie A.; Semper, Cameron; Zimmerly, Steven
Abstract : The cover image, by Steven Zimmerly et al., is based on the Advanced Review Group II introns: versatile ribozymes and retroelements, DOI:10.1002/wrna.1339 . Abstract : The cover image, by Steven Zimmerly et al., is based on the Advanced Review Group II introns: versatile ribozymes and retroelements, DOI:10.1002/wrna.1339 .